Ethical challenges of parenting in the digital - seyed mohamad hoseini sourski; Hossein Rezaei (اخلاق وحیانی)
Ethics have always played a fundamental and influential role in human life. One of the most critical domains where ethics manifest prominently is in parenting and parent-child relationships. With the rapid expansion of digital technologies, the emergence of social media platforms, and the ease of access to internet services and virtual spaces, the scope of parenting has extended from the real world to include the virtual sphere. In this context, conscientious parents are tasked with equipping their children with the necessary skills for the safe, responsible, and ethical use of digital technologies. By adhering to specific principles and adopting responsible parenting strategies in the digital realm, they aim to safeguard the moral and psychological well-being of their children. However, the need for monitoring, controlling, and limiting technology use introduces a range of ethical challenges in the parent-child relationship. This study adopts an analytical approach to identify and examine the ethical challenges of parenting and supervising children in the digital age. Among these challenges are the violation of children's privacy, improper handling of harmful situations in virtual spaces, the conflict between parental control and children's self-regulation, and the effects of these issues on children's creativity and moral self-motivation.